MY DREAMS OF TRAVELING AROUND THE WORLD - Zakirjanov Muhammadkadir Ikromjon ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: Travel takes us out of our comfort zones and inspires us to see, taste and try new things. It constantly challenges us, not only to adapt to and explore new surroundings, but also to engage with different people, to embrace adventures as they come and to share new and meaningful experiences with friends and loved ones.